Optical properties of indocyanine green under ultrasound treatment - Mohammed Attia; Joanna Cao; Ruth Chan; Jian Ling; Jing Yong Ye (Journal of Photochemistry and Photobiology, 2020)
Indocyanine green (ICG) is an FDA-approved and commercially available dye that exhibits fluorescence in the near infrared region. ICG has been utilized as a contrast agent for a wide range of applications in biomedical research and clinical diagnostics, particularly in-vivo imaging. The optical properties of ICG are known to be sensitive to its concentration, the temperature, and the presence of different serum proteins in its solutions. In this paper, we report a notable effect on modifying the optical properties of ICG using ultrasound (US) waves. Mid-frequency US waves at different powers were applied to ICG and bovine serum albumin (BSA) dissolved in a phosphate buffered saline (PBS) solution. Our experimental results indicate a significant increase of the absorption and fluorescence of ICG dissolved PBS in the presence of BSA when the applied US is above a threshold pressure (4.4 MPa). In contrast, ICG samples without BSA showed no enhancement effect on ICG's absorption or fluorescence emission after US treatments under the same condition. In addition, the stability of the ICG samples after the US treatments was also measured. Significantly improved stability of ICG samples in the presence of BSA under the US treatment with a pressure higher than 4.4 MPa was observed. The mechanism of the enhancement effects of US on the optical properties of ICG has been discussed in this paper.